MODERATION VARIABLES FOR STOCK RETURNS, TRADING ACTIVITY, AND FINANCIAL PERFORMANCE - Masno Marjohan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
The purpose of this study is to determine the financial performance that influences transaction volume activity and the financial performance that influences stock returns as moderation in retail. The data used by the researchers is secondary data in the form of annual accounts of retail companies listed on the Indonesian Stock Exchange. This survey method, which targets 21 trading companies, uses multiple regression analysis methods. The two dependent variables in the analysis of financial performance have a negative impact on TVA and are not significant, but the intervening variables do not affect stock returns and do not have a large impact. Together or concurrently, they had no positive or insignificant impact on TVA, but the remaining 72.1% were influenced by other factors not examined in this study and together or concurrently had a positive effect on stock returns. had a significant effect, whereas the remaining 85.9% were affected. by other factors not considered in this study. The study combines financial performance with trading volume and stock returns to give investors a more comprehensive understanding of their stock investment decisions to achieve capital gains. Practical/political implications (optional): The results have practical and functional implications for investors, especially when analyzing purchase price decisions for selected stocks. Stock selection should be taken into account in investment analysis. When investors are not convinced that financial performance is a material factor. This investor maximizes investment returns (capital gains) in the future.